Creative Writing Module of Fantasy Story for VII Graders - Fika Rahmawati; Muakibatul Hasanah; Wahyudi Siswanto (Universitas Negeri Malang, 2018)
Abstract: One of the skills that must be mastered by students is creative writing. Creative writing lesson at the Junior Hih School level is still constrained since the module that specifically teach students creative writing is limited. This study aims to (1) produce a creative writing module of fantasy story for VII graders and (2) test the effectiveness of the module to improve students' creative writing skills. The development procedure used a 4-D model consisting of four stages of development, namely (1) definition, (2) design, (3) development, and (4) dissemination. Expert and practitioner test results stated that the module is suitable for creative writing lesson which is seen from the content, systematic presentation, language, and graphic design aspect. Field test results stated that the product is effective for improving students' creative writing skills. Key Words: module, creative writing, fantasy story, class VII student Abstrak: Salah satu keterampilan yang perlu dikuasai siswa adalah menulis kreatif. Pembelajaran menulis kreatif di jenjang SMP masih terkendala oleh kurangnya modul yang khusus mengajari siswa menulis kreatif. Penelitian ini bertujuan untuk (1) menghasilkan modul menulis kreatif cerita fantasi untuk siswa kelas VII dan (2) menguji keefektifan modul tersebut untuk meningkatkan keterampilan menulis kreatif siswa. Prosedur pengembangan menggunakan Model 4-D yang terdiri atas empat tahap pengembangan, yakni (1) tahap pendefinisian, (2) tahap perancangan, (3) tahap pengembangan, dan (4) tahap penyebarluasan. Hasil uji ahli dan praktisi menyatakan bahwa modul layak digunakan sebagai modul menulis kreatif cerita fantasi baik dari aspek isi, sistematika penyajian, penggunaan bahasa, maupun kegrafikaan. Hasil uji lapangan menyatakan produk tersebut efektif untuk meningkatkan kemampuan menulis kreatif siswa. Kata kunci: modul, menulis kreatif, cerita fantasi, siswa kelas VII